Together apart? Stocktaking of the process of labour market integration in the border region between Germany, Poland and the Czech Republic - Oliver Schwab; Kathleen Toepel (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2006)
This article explores the process of labour market integration in the border region of Saxony, Poland and the Czech Republic. The underlying understanding of integration is combining institutional factors and the behaviour of market players. The sources of this conceptual framework stem from political science on the one hand and economics on the other. This article has two aims: firstly, we want to identify the likely development of the labour markets in the region concerned, secondly, we wish to gain some information about the interrelation of the different factors mentioned. The article is based on a number of empirical studies with three main sources: firstly official statistical data, secondly surveys, and finally results from evaluation studies. Concerning the prospects of the integration of regional labour markets, the article states that the integration process will take some time. Institutional thresholds consist not only of the transition regulations, but also of a misfit between the different national systems (e.g. of vocational education). In any case, the entire region is expected to be affected by common development trends, such as losing population due to the migration of mainly younger people. In the players' perception so far, a mutual understanding of the problems has not been reached. Whilst Polish and Czech players emphasise the opportunities to be gained from integration, the German players are cautious. However, some of their fears seem to be exaggerated: migration will most likely be oriented not towards the border region, but to the centres, only commuting might be a subject to deal with. Efforts to support actively the integration of the labour markets have so far shown only very limited results. All in all integration processes will take time. Not only does the institutional misfit need to be overcome (or at least interfaces need to be defined), but also perceptions and attitudes (at least on the German side of the border) need to be changed.
Keywords: 330; europäische Integration; Grenzgebiet; EU-Osterweiterung; Arbeitsmarktentwicklung; regionaler Arbeitsmarkt; grenzüberschreitende Zusammenarbeit; internationale Zusammenarbeit; Einwanderung; Grenzpendler; Landflucht; demografischer Wandel; institutionelle Faktoren; Arbeitsmigration; Integrationspolitik; internationale Wanderung; Ost-West-Wanderung; Bundesrepublik Deutschland; Sachsen; Polen; Tschechische Republik; Europäische Union; Osteuropa; Mitteleuropa